2023
DOI: 10.1002/suco.202200473
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties, durability performance and interlayer adhesion of 3DPC mixtures: A state‐of‐the‐art review

Abstract: In this study, the strength and durability performance of 3D printing concrete mixtures (3DPC) were examined in terms of the materials used in their production and printing process parameters (interlayer interval time, printing speed, and nozzle shape). Due to the anisotropic nature of 3DPC, it was understood that the compressive strength depends on the loading direction. It was emphasized that it is necessary to control the shrinkage behavior of 3DPC mixtures due to the lack of formwork and the high dosage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 145 publications
(293 reference statements)
0
3
0
Order By: Relevance
“…As a result of the addition of 1.5% of NT with 28- and 38-nm particle sizes to the mixture, it was understood that the need for HRWRA in PSCM mixtures increased by 29% and 14%, respectively. It is thought that the need for HRWRA is higher due to the increase in the wettable surface area (Durgun et al 2022 ; Mardani-Aghabaglou et al 2018 ; Özen et al 2021 ; Şahin et al 2022 , 2020 ; Şahin and Mardani 2023b ) and the amount of adsorbed water due to the increased surface area due to the decrease in NT particle size (Kuo et al 2006 ). It was reported by Chen et al ( 2012 ) that the rapid hardening potential, which is directly dependent on the NT particle size and utilization ratio, directly affects the consistency retention capacity of the mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the addition of 1.5% of NT with 28- and 38-nm particle sizes to the mixture, it was understood that the need for HRWRA in PSCM mixtures increased by 29% and 14%, respectively. It is thought that the need for HRWRA is higher due to the increase in the wettable surface area (Durgun et al 2022 ; Mardani-Aghabaglou et al 2018 ; Özen et al 2021 ; Şahin et al 2022 , 2020 ; Şahin and Mardani 2023b ) and the amount of adsorbed water due to the increased surface area due to the decrease in NT particle size (Kuo et al 2006 ). It was reported by Chen et al ( 2012 ) that the rapid hardening potential, which is directly dependent on the NT particle size and utilization ratio, directly affects the consistency retention capacity of the mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…Serious requirements, especially regarding the rheology of 3DPC, have been noted [ 11 ]. While fresh concrete should have relatively lower yield stress and viscosity values during the pumping and extrusion process, it was reported that after extrusion it should have a higher yield stress, viscosity value and an optimum structural build-up rate in order to resist parameters that may cause possible deformation [ 10 , 12 ]. Şahin and Mardani [ 9 ] reported that the parameters that can create deformation mentioned are as follows: (i) own weight, (ii) weight of the upper layers, and (iii) high extrusion pressure, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In studies conducted in the literature, it can be seen that both the thixotropic properties and strength properties of 3DPC mixtures can be positively affected by the addition of these agents [ 12 ]. SF and hydroxypropyl methylcellulose were proven to be effective viscosity modifying materials that positively affect the buildability and thixotropic behavior of 3DPC mixtures [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies showed that the quality of the attached mortar is improved when the recycled aggregates are derived from enhanced performance parent concrete possessing relatively higher strengths [ 19 , 21 , 22 ]. The concrete mechanical properties may be improved by reducing the water-to-binder ratio (w/b) [ [23] , [24] , [25] , [26] ]. For mixing, several authors recommended pre-saturating the recycled aggregate fraction in order to reduce the exchange of moisture inside the concrete [ 15 , 18 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%